2023
DOI: 10.21203/rs.3.rs-2577831/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Silver nitrate (AgNO3) and Pyrazinamide (PZA) as ethylene inhibitors ameliorate in vitro salt tolerance of tomato (Lycopersicon esculentum L) plant.

Abstract: The purpose of this research was to find out how in vitro culture of tomato explants respond to salt stress by silver nitrate (AgNO3) and pyrazinamide (PZA) as ethylene inhibitors. Tomato seedlings were grown on MS medium containing NaCl (0, 100, 150 mM) and supplemented with AgNO3 (0, 2, 4, mg. L-1) and pyrazinamide (PZA) (0, 2, 4,mg. L-1) to study growth parameters and antioxidant enzymes responses. Salt-stressed plants showed limited growth and a significant decrease in fresh and dry weight. Salinity accele… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Ethylene, a phytohormone, is essential for regulating various aspects of plant growth and development. Several studies have shown that the buildup of ethylene in culture media can lead to reduced growth and morphological changes in plants [22][23][24]. To counteract these effects, compounds such as AgNO3, a silver salt, have been utilized as anti-ethylene agents in vitro cultures [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Ethylene, a phytohormone, is essential for regulating various aspects of plant growth and development. Several studies have shown that the buildup of ethylene in culture media can lead to reduced growth and morphological changes in plants [22][23][24]. To counteract these effects, compounds such as AgNO3, a silver salt, have been utilized as anti-ethylene agents in vitro cultures [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Inhibiting ethylene biosynthesis and signaling has emerged as a promising approach to alleviate the negative effects of salinity stress in plants. The ability to modulate ethylene responses by ethylene inhibitors, such as PZA and AgNO3, has been reported in some plant species (Zarei and Ehsanpour 2023). PZA as a competitive inhibitor of ACS and ACO enzymes responsible for the rate-limiting step in ethylene biosynthesis, while AgNO3 interferes with ethylene signaling by forming a nonfunctional complex with ethylene receptors.…”
Section: Introductionmentioning
confidence: 99%